Pengembangan Perpustakaan Umum Bahagia Mendawai melalui Kegiatan Kreatif dan Pengelolaan Perpustakaan Berbasis Digital - Nurrahim, Muhammad Fakhri; Shalahuddin, Ahmad; Pualam, Akira Putri; Bella, Alifa Tauris Miranda; Irawan, Valinka Dewi Fortuna; Saputra, Ahmad Ernanda Dwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The community service activity is based on the problem of a lack of creative activities and understanding of current technology in the 4.0 era. Observations and interviews with the Chair of the Perpustakaan Bahagia Mendawai, revealed that many children living on the coast of the Sungai Kapuas, particularly in Kampung Caping, have minimal understanding of technology. Despite the library having facilities such as four computers, but there are no teachers who have free time to teach the children in the village. To address this, nine work programs will be implemented to enhance children's abilities in using digital technology and educational approaches through creative activities. These programs include Beads Workshop, Microsoft Word Training, Design Training via Canva, Education on Saving and Practicing Making Piggy Banks, Daily Schedule Making Training, Collage Crafts, DIY Used Bottles, Social Media Management, and Bahagia Mendawai Library Administration Management. The goal is to transform children who have never used a computer into proficient users, especially in Microsoft Word. The use of computers in learning activities plays a crucial role in increasing literacy by requiring children to read books before taking typing training and then accessing information more widely. This helps develop the reading and writing skills needed in the current 4.0 era. The aim is to contribute positively to creating a young generation skilled in technology use, fostering creativity, and promoting strong literacy from an early age.